Ja, Ty, Inny – dialog? - Żółkowska, Teresa (Wydawnictwo Naukowe UAM, 2013)
Dialogue is a notion often used both in scientifi c discussions and in colloquial speech. The biggest interest of dialog may stem from the fact that the philosophy of dialogue promotes new ways of learning and understanding the world. The article furnishes a comparison of M. Buber’s and E. Levinas’ views concerning dialogue. Both M. Buber and E. Levinas highlight the meaning of a new dimension of cognition, pointing at the meaning of dialogic relations. However, they differ in their interpretation of dialogues between Me, You and The Other. In Buber’s interpretation, dialogue is a situation of discourse, a situation of encounter. Dialogue takes place in a face-to-face relation, in a situation of commitment, engagement and reciprocity. The conditions of dialogue are symmetry, balance and flexibility. Levinas, however, thought that the Other is always different than I. In his opinion of the dialogic, Me-You are not partners. You is higher than I. For Levinas dialogue occurs in a situation of asymmetry, inequality between Me and You, absence of freedom, a need for sacrifi ce and taking the responsibility of Others. Questions that arise relate to whether dialogue may occur freely in such circumstances. Is Levinas really a philosopher of dialogue?
Me, You, the Other – a Dialogue?
Keywords: dialogue; M. Buber’s dialogic; E. Levinas’ philosophy of dialogue